2014
DOI: 10.1016/j.drugalcdep.2013.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the prevalence of adult ADHD in treatment seeking substance use disorder patients: Results from an international multi-center study exploring DSM-IV and DSM-5 criteria

Abstract: BackgroundAvailable studies vary in their estimated prevalence of attention deficit/hyperactivity disorder (ADHD) in substance use disorder (SUD) patients, ranging from 2 to 83%. A better understanding of the possible reasons for this variability and the effect of the change from DSM-IV to DSM-5 is needed.MethodsA two stage international multi-center, cross-sectional study in 10 countries, among patients form inpatient and outpatient addiction treatment centers for alcohol and/or drug use disorder patients. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
147
4
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(174 citation statements)
references
References 37 publications
18
147
4
5
Order By: Relevance
“…The main reason for this inconsistency may be that we used the Adult ADHD Scale as the gold standard, whereas Roncero et al (8) used Conners' Adult ADHD Diagnostic Interview for DSM-IV (CAADID). In a multicenter international study, the prevalence of DSM-IV and DSM-5 adult ADHD varied for DSM-IV from 5.4% (CI 95%:2.4-8.3) for Hungary to 31.3% (CI 95%:25.2-37.5) for Norway and for DSM-5 from 7.6% (CI 95%:4.1-11.1) for Hungary to 32.6% (CI 95%:26.4-38.8) for Norway (50). Thus, like the cutoff score of ASRS, prevalence rates of ADHD may also differ according to the population that is studied and the language of the scale.…”
Section: Discussionmentioning
confidence: 99%
“…The main reason for this inconsistency may be that we used the Adult ADHD Scale as the gold standard, whereas Roncero et al (8) used Conners' Adult ADHD Diagnostic Interview for DSM-IV (CAADID). In a multicenter international study, the prevalence of DSM-IV and DSM-5 adult ADHD varied for DSM-IV from 5.4% (CI 95%:2.4-8.3) for Hungary to 31.3% (CI 95%:25.2-37.5) for Norway and for DSM-5 from 7.6% (CI 95%:4.1-11.1) for Hungary to 32.6% (CI 95%:26.4-38.8) for Norway (50). Thus, like the cutoff score of ASRS, prevalence rates of ADHD may also differ according to the population that is studied and the language of the scale.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis of 29 predominantly US studies estimated a pooled ADHD prevalence rate of 23% in mixed SUD populations [1]. A rate of 14% (5–31% between countries) was reported by the International ADHD in Substance use disorder Prevalence (IASP) study [6]. This is the largest clinical study so far to evaluate ADHD and comorbid disorders in treatment-seeking adults with SUD [7].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients were young adults, indicating that alcohol misuse with or without ADHD tends to commence early in life. In a similar study, the mean age of patients with ADHD varied between 37 and 43 years [18]. Similarly, a study conducted by Ganesh et al [19] on 240 patients observed for early onset of SUD the majority of cases (N=209) had a mean age of 32.75 (SD ±11.14) years.…”
Section: Discussionmentioning
confidence: 80%